Jahresbericht 1992 - Kunstgesellschaft Luzern. - Kunstmuseum Luzern, Luzern (Luzern : Kunstgesellschaft Luzern, 1993)
Walther, Franz Erhard ; Fries, Pia ; Nordman, Maria ; Gober, Robert ; Smith, Kiki ; Gonzalez-Torres, Felix ; Alma, Alfred Hofstetter ; Käch, Markus ; etc.
Duits
boek